Food adulteration - Monsch, Helen (My University, 1904)
Introduction: Many housekeepers spend a large part of their time plannining and preparing daily meals, in order to have them as appetizing and digestible as possible, but few of them stop to think much less to examine the article of food obtained from the grocer, to be sure that they have not a substitute. Some are willing to contentedly pay a high price for a poor article, without questioning it at all, while others demand such cheap food, that the only way it can be furnished them is in a form so adulterated, not only with cheap, but sometimes even with poisonous substances, as to make it unfit for use. There are, in this world, all types of people, among them men who are willing to do anything for money, and some of these, in order to satisfy this demand for cheap food, started the business of adulteration, and others have followed, so that to-day there is scarcely an article of food that is not tampered with.
Citation: Monsch, Helen. Food adulteration. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Food; Food Quality; Diet; Nutrition; Theses